PROTOCOL DEVELOPMENT FOR THE DETECTION OF MICRODELETIONS IN THE AZF LOCUS OF THE Y CHROMOSOME - Kairzhanova , A.D.; Abisheva , G.D.; Popova , O.A.; Kamalova , D.K.; Shevtsova , E.S.; Shevtsov , A.B. (Eurasian Journal of Applied Biotechnology, 2015)
Microdeletions in the long arm of the Y chromosome are common causes of male spermatogenesis disorders. The frequency of the AZF locus microdeletions is approximately1 in 1000–1500 males. Such deletions of the Y chromosome are identified in 11% of males with azoospermia and in 8% of males with severe oligospermia. The aim of this study was to develop a multiplex polymerase chain reaction (PCR) protocol for the detection of microdeletions in the AZF locus of the Y chromosome. Based on the literature, the following sequence tagged site (STS) markers were used for development of the PCR protocol for screening the AZF locus microdeletions: AZFa-sY86 иsY84, AZFb-sY127 and sY134, AZFс-sY254 and sY255. As a control, the presence of Y chromosome short arm fragments in the genomic DNA were assessed using the SRY gene sequence and ZFY/Х as an internal control of the PCR. Confirmation of the developed protocol was performed with 40 DNA samples. The protocol recommended by The European Academy of Andrology was used as a complementary method to confirm our results. The results from both methods indicate the specificity and high demand of the developed PCR protocol.